Strategic plan for Sheryl John Charisse Merchandising - Sardido, Sheryl A.; Ellson, Adela G.; Pabularcon, Liza N. (Davao City School of Management, University of the Philippines Mindanao, 2007)
Sheryl John Charisse (SJC) Merchandising offers a wide range of imported decorative items to accentuate one?s home. After two decades of selling imported luxury items to the upper segment in the market, SJC is planning to expand and grow its market share. It has already reached its maturity and as one of the pioneers of the imported home decors and chandeliers business in Davao City, the owner needs to re-engineer their strategies to keep their products at pace with the recent trends and developments in the environment to maintain its competitive edge in the market. A strategic plan will allow Sheryl John Charisse Merchandising to assess its existing practices and procedures, expand its horizons and grab a bigger share in the market. This will help enhance the company?s marketability and visibility nationwide. This strategic plan applies the classic "Input-Process-Output" Model and Strategy-Formulation Analytical Framework of Fred David (2000) in coming up with a proposed strategy for Sheryl John Charisse Merchandising. The "Input" phase will include the relevant forces gathered from the general situation review and data gathered from the firm considering its vision, mission, and goals. The "Process" phase is visible in each stage of the general framework as the entire process in this framework will be aligned and matched with the company?s objectives. Lastly, the "Output" of this paper is to come up with the most likely strategic option for SJC in expanding its horizons nationwide. The proposed strategy has implementing programs in each functional area of the business aligned to the company's objectives. Monitoring & control mechanism are put in place using the Balanced Scoreboard Approach developed by Dr. Kaplan and Dr. Norton to evaluate implementing programs and capture the lead indicators of the company's future performance. Future value of the proposed expansion program will be driven by four key perspectives: (1) financial perspective; (2) customer perspective; (3) internal perspective; and (4) learning and growth perspective. Progress in each of these perspectives will be measured to gauge the timeliness of the strategy implemented. Key result areas of the selected strategy and its corresponding performance indicators will validate the proposed strategy's appropriateness to the company's objectives. Financial constraints and existing capabilities of the company will be evaluated and planned accordingly in preparation for the realization of the proposed strategic expansion program. Actions taken will be backed-up by contingencies if the proposed expansion strategy has an unfavorable outcome. Take for instance building an additional showroom as a move in the proposed expansion may be capital intensive. As an alternative course of action to this capital-intensive project of building a showroom, the company could improve visibility by expanding its horizon through aggressive marketing. Furthermore, the business could also expand its distribution network by keeping their supply chain networks efficient and taking collaborative and strategic alliances with the right people at the right place and time. In a competitive world of business, it's about time for SJC to get out of its shell and look at the bigger picture and see what other programs it could possibly initiate to enhance efficiencies across the chain to better serve its households and continuously enjoy the premium comfort of royal elegance --- living up to its vision, mission and goals. SJC needs to strategically manage and continually maintain good relationship with its business partners in upholding its "ROYAL HIGHNESS."
Thesis (Master in Management)--University of the Philippines Mindanao, April 2007.